The use of multidisciplinary teams, electronic health records tools, and technology to optimize heart failure population health. (May 2022) - Martyn, Trejeeve; Montgomery, Robert A.; Estep, Jerry D.
Abstract : Purpose of review: Given the limited population level, adoption of optimal therapy that has been shown in recent clinical trials and heart failure registries, efforts to rapidly and safely improve adoption of guideline-directed medical therapy for heart failure should be prioritized. Opportunities to leverage remote monitoring technology, the electronic health record (EHR), and multidisciplinary teams to improve heart failure care merit review. Recent findings: Dedicated multidisciplinary teams employing algorithmic medication titration schema have shown better efficacy than clinician alerts or quality initiatives that focus on education and audit-feedback processes alone. Technology that enables invasive pressure monitoring and wearable devices that transmit physiologic data have the potential to predict decompensation and allow for early intervention by alerting clinicians to signs of congestion/clinical worsening but further real-world data is needed to prove efficacy and develop effective treatment protocols. Summary: The combination of technology, multidisciplinary teams, and identification of populations for intervention using the EHR will be central to impactful innovation in heart failure population health and prevention of avoidable morbidity. Novel approaches to study implementation efforts including cluster randomized trials are needed.